ANALISIS PENGARUH NILAI TAHANAN PEMBUMIAN TITIK NETRAL TRANSFORMATOR TERHADAP PERUBAHAN THD ARUS DAN RUGI-RUGI DAYA DI RSUD KLUNGKUNG - Satcitananda P, I G.B.; Rinas, I W.; Janardana, I G.N. (Jurnal SPEKTRUM, 2020)
Harmonics causes an increase in the current flowing in the neutral wire due to the use of unbalanced non-linear loads. THDi simulation was conducted in this study using MATLAB Simulink software and calculating power losses. Based on the measurement results it is known that THDi transformer one exceeds the standards set by IEEE 519-2014. THDi simulation results in the existing conditions show the percentage of phase R of 17.27%, S phase of 16.40%, phase T of 16.24% with a current flowing on a neutral wire of 19.64 A. Based on the results of simulations with earth resistance 11? shows the percentage of THDi in the R phase 15.69%, S phase 14.70%, T phase 9.83% and the current flowing on the neutral wire is 1.013 A. When the earth resistance is changed to 8? THDi in the R phase by 15.62%, the phase S 14.67%, T phase 9.81% with current flowing on neutral wire 1,297 A. While the earth resistance is reduced to 4? THIn the R phase 13.57%, S phase 14.51%, T phase 9.80% and the current flowing on the neutral wire is 2,518 A. The power losses in the one-time transformer when the existing conditions are 8,796 kW, while the earth resistance 11? is 6,079 kW, while the ground resistance 8? is 6,032 kW, and when 4? is 5,880 kW.